Comparative web accessibility evaluation of saudi government websites for compliance with wcag 1.0 and wcag 2.0 using automatic web accessibility tools - Akram M.; Sulaiman R.B. (Little Lion Scientific, 2023)
Web sites are an essential source of information in education, social life, employment, government, commerce, e-shopping, healthcare etc. As the Saudi government is continuously introducing many new eservices for his citizen and residents, but still many disable peoples are not able to get full advantage from these e-services due to poor web accessibility. According to the World Health Organization (WHO) reports, more than one billion people live with different kinds of disabilities all over the world. Saudi Arabia has 720,000 disabled people which are about 4% of the total Saudi population. Many researchers documented that government official paid very little attention towards the need for disabled people during the planning and implementation of web projects. Therefore, it is essential that all citizens and resident of Saudi Arabia must have equal opportunities to access and benefit from all e-government recourses. The objective of this study is to evaluate and compare the web accessibility of Saudi government websites by using automatic web accessibility tools. Fifteen Saudi government websites were selected, and the homepage of each website was evaluated for web accessibility and HTML and CSS validity. Results generated by automatic accessibility tools exposes that most the government websites have serious accessibility problems which hinder the disable users to access the web contents completely. Furthermore, automated web accessibility tools are not able to report some accessibility issues found by users because it is difficult for accessibility analysis tools to understand the way web contents interact with assistive technologies used by disabled users. However, findings in this study demand to do extensive research by involving the disabled users, web developers and accessibility experts in web accessibility evaluation process to improve the website accessibility and overall quality of websites. 2005 ongoing JATIT & LLS.